Overconfidence in Understanding of How Electronic Gaming Machines Work Is Related to Positive Attitudes - Philander, Kahlil S.; Gainsbury, Sally M. (Frontiers in Psychology, 2021)
Previous research has demonstrated that attitudes are a primary determinant of intention to gamble on electronic gaming machines (EGMs) consistent with the Theory of Reasoned Action. This paper aims to address how biases in judgment can contribute to attitudes and subsequently behaviour, including maladaptive problematic gambling behaviour. We take a novel approach by viewing overconfidence in one’s understanding of how outcomes are determined on EGMs as an indication of cognitive distortions. The novelty of this paper is further increased as we compare attitudes to existing EGMs with novel EGMs which include a skill component, referred to as skill gaming machines (SGMs). In Study 1, 232 US-based participants were recruited online who were shown various EGMs and SGMs and asked a series of questions about perceived skill and chance in determining outcomes to assess their understanding, then were asked their confidence in their understanding, attitudes towards the machines and they completed the Problem Gambling Severity Index. In Study 2, 246 Australian participants were recruited through community and university student samples; they attended a laboratory where they were randomly allocated to play a real EGM or SGM without money and completed the same measures as in Study 1. In Study 2, participants were randomly told that the outcomes on the machine they would play were determined entirely by chance, skill, or a mixture of both. In both studies there was a relationship between overconfidence in EGM understanding and positive attitudes towards EGMs, but no such relationship with SGMs. There was no impact of demographics, problem gambling severity, or labelling of machines on this relationship. These initial findings suggest that in contrast to a tendency for individuals to over-estimate their knowledge of how EGMs work, individuals are cautious in their accuracy of understanding SGMs. Further research is needed, however, the findings may indicate that when faced with a novel activity, individuals have less well-developed biases, or alternatively, that activities with more interactivity and complexity are less likely to lead to cognitive biases than randomly-determined games given human biases to look for patterns.